2009
DOI: 10.1182/blood-2008-03-139923
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A induces G-CSF expression and neutrophilia via Toll-like receptor 2

Abstract: The acute-phase protein serum amyloid A (SAA) is commonly considered a marker for inflammatory diseases; however, its precise role in inflammation and infection, which often result in neutrophilia, remains ambiguous. In this study, we demonstrate that SAA is a potent endogenous stimulator of granulocyte colonystimulated factor (G-CSF), a principal cytokine-regulating granulocytosis. This effect of SAA is dependent on Toll-like receptor 2 (TLR2). Our data demonstrate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
135
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 53 publications
9
135
0
1
Order By: Relevance
“…2). These findings are consistent with previous reports, which used TLR2-and TLR4-deficient mice to show that SAA can activate TLR2 and TLR4 receptors (35)(36)(37)(38). The scavenger receptor CD36 has been recently shown to function as a receptor for SAA and to mediate the expression of IL-8 in response to SAA (39).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…2). These findings are consistent with previous reports, which used TLR2-and TLR4-deficient mice to show that SAA can activate TLR2 and TLR4 receptors (35)(36)(37)(38). The scavenger receptor CD36 has been recently shown to function as a receptor for SAA and to mediate the expression of IL-8 in response to SAA (39).…”
Section: Discussionsupporting
confidence: 82%
“…SAA has been shown to interact with several cell-surface receptors, including formylpeptide receptor-like 1 (FPRL1) (5,33,34), TLR4 (35), TLR2 (36)(37)(38), and the scavenger receptor CD36 (39). The ability of SAA and TLR4 agonist LPS to induce IL1B expression was studied first.…”
Section: Saa Induces Synthesis Of Pro-il-1b Through Tlr2 and Tlr4mentioning
confidence: 99%
“…In addition to FPR2, several other targets have been reported as specific receptors for SAA, including receptor for advanced glycation end products (Yan et al, 2000), the HDL receptor, scavenger receptor class B type I (Cai et al, 2005), CLA-1 (CD36 and LIMPII analogous-1), human orthologue of the Scavenger Receptor Class B Type I (Baranova et al, 2005), P2X7 (Christenson et al, 2008), TLR4 (Sandri et al, 2008), and TLR2 (He et al, 2009). Because we found that SAA stimulated CCL2 production via a PTX-insensitive pathway, we confirmed a role for FPR2 in SAA-induced cellular signaling in HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Saa3, is a major acute-phase protein that can act as a chemoattractant for phagocytes (35) and recently was shown to promote Th17-mediated allergic asthma through the activation of the NLRP3 inflammasome complex (36). Our data showed that this gene was significantly upregulated following Flu infection, with an additional 2-fold increase following HDM exposure during the EP that was sustained through the LP, where we observed a 5-fold difference in expression level between Flu-and Flu+HDM-treated mice (Tables VI, VII).…”
Section: Discussionmentioning
confidence: 99%